Formulation of the diagnosis, selection, and coding according to ICD-10 of the initial cause of death in fatal outcomes in patients with transplanted organs - Svishcheva, Polina O.; Kanibolotskiy, Alexander A. (Russian Journal of Forensic Medicine, 2023)
BACKGROUND: Due to a lack of unified recommendations, difficulties often arise when making diagnoses, as well as selecting and coding according to ICD-10 of the initial cause of death in cases of fatal outcomes of patients after organ transplantation. AIM: To offer practical recommendations on the formulation of diagnoses, selection, and coding according to ICD-10 of the initial cause of death in cases of fatal outcomes based on the experience of the pathology department at the N.V. Sklifosovsky Research Institute of Emergency Medicine. MATERIALS AND METHODS: Sixty autopsy reports of fatal outcomes in patients after organ transplantation at the N.V. Sklifosovsky Research Institute of Emergency Medicine for 7 years (20162022) were analyzed. RESULTS: Based on the results of the analysis, taking into account the literature data, recommendations for making diagnoses, selecting, and coding according to ICD-10 of the initial cause of death of patients after organ transplantation were formulated. CONCLUSION: The developed recommendations on the formulation of diagnoses in patients death cases after organ transplantation can be used in the daily practice of forensic medical experts.